Public–private partnerships in international agricultural research - Spielman, David J.; Hartwich, Frank; von Grebmer, Klaus (International Food Policy Research Institute, 2007)
Public-private partnerships (PPPs) in agricultural research and development are increasingly viewed as an effective means of conducting advanced research, developing new technologies, and deploying new products for the benefit of small-scale, resource-poor farmers and other marginalized groups in developing countries. There are, however, few studies that empirically establish whether PPPs fulfill this role in the context of developing-country agriculture. This brief presents the results of a study that examines how PPPs in agricultural research stimulate greater investment in pro-poor innovation in developing country agriculture. The brief provides policymakers, research managers, and business decisionmakers with a better understanding of how such partnerships operate, what types of challenges they face, and how their operation can be improved to make a greater contribution to food security and poverty reduction.